Young People’s Autonomy and Psychological Well-Being in the Transition to Adulthood: A Pathway Analysis - Melendro, Miguel; Campos, Gema; Rodríguez-Bravo, Ana Eva; Arroyo Resino, Delia (Frontiers in Psychology, 2020)
Young people transition to adulthood via diverse pathways; among the most significant are those marked by education, employment, or social disadvantage. These pathways are determined, to a large extent, by the level of autonomy and well-being young people develop to help them face their own realities. The aim of this study is to analyze the relationship between young people’s autonomy and psychological well-being as key factors in the transition to adulthood, and the relationship these factors have with the main pathways followed during transition. To this end, a total sample of 1148 Spanish and Colombian subjects, aged between 16 and 21, completed the Transition to Adulthood Autonomy Scale (EDATVA) and Ryff’s Six-Factor Model of Psychological Well-being. Correlations and differences between scores were subsequently analyzed. In turn, young people were asked to identify the pathway followed in their transition to adulthood: education, employment, or social disadvantage. Results from the three pathways in the transition to adulthood show a trend in which higher levels of well-being correspond to higher levels of autonomy. In general, the results for the young people on the education pathway show high levels of autonomy and well-being, as well as a significantly higher level of critical thinking compared to young people on other pathways. The scores from employed young people reveal a greater capacity for self-organization in relation to the other two pathways. The results for disadvantaged young people show significantly greater socio-political engagement than that of young people on the education and employment pathways. However, the latter is also the group with the lowest level of psychological well-being. These results provide elements for a better understanding of young people’s different ways of transitioning to adulthood and constitute an important point of reference for future research. They also provide relevant data to guide educational, psychological, and social interventions that could be performed with this population group.